Workshop Advances in Shape Grammars: Implemented Shape Grammars - Pauwels, P; Eloy, S. (Workshop Advances in Shape Grammars: Implemented Shape Grammars, 2016)
Proceedings of the Workshop on "Advances in Shape Grammars: Implemented Shape Grammars" held in DCC 2016.